The finite element method solution for the right cylindrical tank with non-uniform wall thickness - Maneepai, Satit
A need exists for the development of the Axi-symmetric Stress Analysis (two-dimensional element) that can be used for static analysis of stress distribution in the bodies of axi-symmetric solid structures under axi-symmetric loading. Such two-dimensional elements are required if it is desired to analyze the right cylindrical tank with linear non-uniform wall thickness under the internal pressure. In this thesis the stiffness matrix for the right cylindrical shell element is derived using the shell theory and cylindrical coordinate system.